Big Data Impacting Dynamic Food Safety Risk Management in the Food Chain - Donaghy, John A.; Danyluk, Michelle D.; Ross, Tom; Krishna, Bobby; Farber, Jeff (Frontiers in Microbiology, 2021)
Foodborne pathogens are a major contributor to foodborne illness worldwide. The adaptation of a more quantitative risk-based approach, with metrics such as Food safety Objectives and Performance Objectives necessitates quantitative inputs from all stages of the food value chain. The potential exists for utilization of big data, generated through digital transformational technologies, as inputs to a dynamic risk management concept for food safety microbiology. The industrial revolution in Internet of Things, will leverage data inputs from precision agriculture, connected factories/logistics, precision healthcare and precision food safety, to improve the dynamism of microbial risk management. Furthermore, interconnectivity of public health databases, social media and e-commerce tools as well as technologies such as blockchain will enhance traceability for retrospective and real-time management of foodborne cases. Despite the enormous potential of data volume and velocity, some challenges remain, including data ownership, interoperability and accessibility. This paper gives insight to the prospective use of big data for dynamic risk management from a microbiological safety perspective in the context of the ICMSF conceptual equation, and describes examples of how a dynamic risk management system could be used in real-time to identify hazards and control Shiga toxin-producing E. coli risks related to leafy greens.